Impact of cigarette smoking on early complications after liver transplantation: A single-center experience and a meta-analysis. - Qingshan Li; Yue Wang; Tao Ma; Xuemin Liu; Bo Wang; Zheng Wu; Yi Lv; Rongqian Wu (PLoS ONE, 2017)
While studies have shown that cigarette smoking has negative implications on the long-term outcome following liver transplantation, its role in early complications is inconclusive.The clinical data of 162 consecutive adult patients who underwent elective liver transplantation from January, 2012 to March, 2016 were analyzed. Patients were defined as active smokers, ex-smokers, or non-smokers on the basis of documentation at the time of liver transplantation. The overall complications following liver transplantation were expressed as the comprehensive complication index (CCI). The specific complications such as the incidence of hepatic artery thrombosis, biliary complications, acute kidney injury were also assessed. A meta-analysis was carried out based on results from the present study and 11 published studies.We found that cigarette smoking was not associated with higher CCI scores and smokers did not have a higher risk for developing hepatic artery thrombosis, biliary complications, acute kidney injury after liver transplantation. Meta-analysis confirmed the null association between cigarette smoking and an increased incidence of hepatic artery thrombosis or biliary complications in liver transplant recipients. However, the pooled results showed a significantly higher risk of cardiovascular diseases and de-novo malignancies in smokers following liver transplantation.There is not enough evidence supporting an association between cigarette smoking and early mortality and morbidity after liver transplantation. However, smokers should still be encouraged to quit before and after liver transplantation due to the long-term health benefits of smoking cessation.